Integrating heparan sulfate mimetics into LbL nanofilms as extracellular matrix-like architectures to promote bone tissue regeneration - E. Bullier-Marchandin; L. Rossignol; A. Echalard; S. Morin-Grognet; J. Maucotel; A. Arabo; D. Barritault; G. Ladam; B. Labat (Carbohydrate Polymers, 2026)

Antarctic Geothermal Soils Exhibit an Absence of Regional Habitat Generalist Microorganisms - Stephen E. Noell; Jaber Abbaszadeh; Huw Richards; Marie Labat Saint Vincent; Charles K. Lee; Craig W. Herbold; Matthew B. Stott; S. Craig Cary; Ian R. McDonald (Environmental Microbiology, 2025)
Active geothermal systems are relatively rare in Antarctica and represent metaphorical islands ideal to study microbial dispersal. In this study, we tested the macro‐ecological concept that high dispersal rates result in communities being dominated by either habitat generalists or specialists by investigating the microbial communities on four geographically separated geothermal sites on three Antarctic volcanoes (Mts. Erebus, Melbourne, and Rittman). We found that the microbial communities at higher temperature (max 65°C) sites (Tramway Ridge on Erebus and Rittmann) were unique from each other and were dominated by a variety of novel Archaea from class Nitrososphaeria , while lower temperature (max 50°C) sites (Western Crater on Erebus and Melbourne) had characteristically mesophilic communities ( Planctomycetes, Acidobacteriota, etc.) that were highly similar. We found that 97% of the detected microbial taxa were regional habitat specialists, with no generalists, with community assembly driven by high dispersal rates and drift (25% and 30% of community assembly, respectively), not environmental selection. Our results indicate that for microbial communities experiencing high dispersal rates between isolated communities, habitat specialists may tend to out‐compete habitat generalists.

Roles of cytochromes P450 and ribosome inhibition in the interaction between two preoccupying mycotoxins, aflatoxin B1 and deoxynivalenol - B. Willoquet; G. Mirey; O. Labat; M. Garofalo; S. Puel; M. Penary; L. Soler; A. Vettorazzi; J. Vignard; I.P. Oswald; D. Payros (Science of The Total Environment, 2024)

Influence of an anticline structure on hydrogeological functioning and aquifer interactions in a multilayered aquifer system: the case of Villagrains-Landiras anticline (Gironde, France) - C. Labat; F. Larroque; B. de Grissac; A. Dupuy; M. Saltel; P. Bourbon (Hydrogeology Journal, 2021)

Whole grain in manufactured foods: Current use, challenges and the way forward - Christelle Schaffer-Lequart; Undine Lehmann; Alastair B. Ross; Olivier Roger; Alison L. Eldridge; Edwin Ananta; Marie-France Bietry; Luis R. King; Alice V. Moroni; Sathaporn Srichuwong; Anne-Sophie Wavreille; Robert Redgwell; et al. (Critical Reviews in Food Science and Nutrition, 2017)

Evidence for deterministic chaos in long-term high-resolution karstic streamflow time series - David Labat; B. Sivakumar; A. Mangin (Stochastic Environmental Research and Risk Assessment, 2016)